Mengimplementasikan tahadduts bi al-ni'mah dalam nilai-nilai syukur yang terkandung dalam ayat 11 surat Ad-Duha dengan menekankan pentingnya mengakui, menghargai, dan memanfaatkan nikmat Allah sebaik-baiknya - Mega Prahesti; Sukiman Sukiman; Mardian Idris Harahap (Indonesian Counselor Association (IKI), 2024)
Tahadduts Bi Al-Ni'mah is an expression of gratitude given to the creator for all the pleasures he has given to his servants. In the values of gratitude, it is a sense of gratitude in life, be it health, wealth, complete physical and others. The meaning of Tahadduts bin-ni'mah is not necessarily by telling it directly with words. Body language or behavior can also be said to show gratitude for the blessings given by Allah which have the potential to build and motivate others to do good too. In this study using the research method The type of research method that the author uses in writing this journal is a library study, namely a study conducted by searching for and discussing literature, journal books and documents related to research using a descriptive qualitative approach. The conclusion of this study is Tahadduts bi Ni'mah is the opinion of the interpreters related to QS. ad-Dhuha verse 11, which is the evidence in the practice of tahadduts bi ni'mah. Tahadduth bi al-ni'mah is a concept in Islam that emphasizes the importance of being grateful for all the blessings given by Allah SWT. This concept means busying oneself by mentioning the name of Allah and being grateful for His infinite gifts.